Externality evaluation: an empirical study of ITRI. (6th May 2009) - Chu, Po-Young; Lin, Yu-Ling; Huang, Chi-Hung; Liu, Tzu-Yar
This study proposes a framework for exploring technology transfer externality of the Industrial Technology Research Institute (ITRI), a national industry technology development research institution in Taiwan over the past three decades. The specific diffusion effects and external impact were quantitatively assessed. High multiplier effects derived from ITRI's spin-off activities are concluded profound. Finally, being a non-profit R&D institution inherited with common properties of public goods, ITRI has created a unique and valuable role to foster Taiwan's high-tech sector. The innovative ITRI model should provide important managerial implications for large R&D institutes as well as emergent countries to initiate and operate projects with unavoidable high risk but desirable enormous externalities.